Nursing of patient with cancer-related insomnia of heart and spleen deficiency type treated with holographic meridian scraping therapy (全息经络刮痧疗法治疗1例心脾两虚型癌因性失眠患者的护理体会) - LU Xiaoli (卢小丽); LIU Shuhong (刘书红); YAN Kang (严康); ZHAO Yanan (赵亚楠); ZHAO Yan (赵燕) (中西医结合护理)
This paper summarized the holographic meridian scraping therapy and nursing interventions for a patient with cancer-related insomnia of heart and spleen deficiency type. Based on the acupoint selection by Traditional Chinese Medicine syndrome differentiation, the holographic meridian scraping therapy and comprehensive nursing interventions including nutrition support, exercise training and psychological care were carried out to relieve insomnia symptoms and improve patient’s quality of life. (本文总结全息经络刮痧疗法治疗1例心脾两虚型癌因性失眠患者的护理经验。基于中医辨证, 选取刮痧部位, 采取全息经络刮痧疗法, 同时配合饮食指导、运动干预、情志护理等常规护理措施, 有效改善肿瘤患者失眠症状, 提高患者生存质量。)